What Is the Maximum Worth of a Dairy Heifer? - Albert de Vries; Russ Giesy (EDIS, 2004)
This fact sheet discusses the factors that determine the maximum price a dairy producer can afford to pay now for dairy heifers when the dairy facility is not operating at full capacity. The approach outlined in this fact sheet is not directly appropriate for making decisions about replacing a cow with a heifer. However, the approach is appropriate when dairy facilities have expanded but are still vacant. Tax implications are ignored and not discussed. This document is AN148, one of a series of the Department of Animal Sciences, Florida Cooperative Extension Service, UF/IFAS. Published March 2004.